The Importance and Dynamics of Effectuation in IT Team Projects - Krawczyk-Bryłka, Beata (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2021)
Objective: To determine how beneficial the implementation of the principles of effectuation is for the effectiveness of project teams and their satisfaction. Research Design & Methods: Quantitative research was carried out on student project teams working in the IT industry, developing solutions at the request of external stakeholders. Proprietary questionnaires were used to measure the variables. The dynamics of the team model was analysed at two stages of project implementation. Findings: Decision-making models used in project implementation do not evolve dynamically. The importance of integrating effect and causal assumptions in various areas of the team’s functioning is confirmed. Implications / Recommendations: The hybrid decision-making model helps boost team effectiveness. Contribution: The analysis of the effectiveness of project teams in the context of effectuation principles is a completely new approach in the Polish literature.